Microbiology of infected pilonidal sinuses. - Brook, I (1989)
Aspirates of pus from infected pilonidal sinuses in 75 patients showed bacterial growth. Anaerobic bacteria only were recovered in 58 (77%) specimens, aerobic bacteria only in three (4%), and mixed aerobic and anaerobic bacteria in 14 (19%). Two hundred and nine isolates were recovered: 147 anaerobes (2.0 isolates a specimen) and 62 aerobes (0.8 a specimen). The predominant anaerobes were Bacteroides sp (81 isolates, including 29 Bacteroides fragilis group) and 51 anaerobic cocci. The predominant aerobes were Escherichia coli (n = 15), Proteus sp (n = 9), group D streptococcus (n = 7), and Pseudomonas sp (n = 7). This study highlights the polymicrobial nature and predominance of anaerobic bacteria in infected pilonidal sinuses.